The role of CAPG in molecular communication between the embryo and the uterine endometrium: Is its function conserved in species with different implantation strategies?. Issue 8 (3rd July 2020) - Tinning, Haidee; Taylor, Alysha; Wang, Dapeng; Constantinides, Bede; Sutton, Ruth; Oikonomou, Georgios; Velazquez, Miguel A.; Thompson, Paul; Treumann, Achim; O'Connell, Mary J.; Forde, Niamh
Abstract: During the preimplantation period of pregnancy in eutherian mammals, transcriptional and proteomic changes in the uterine endometrium are required to facilitate receptivity to an implanting blastocyst. These changes are mediated, in part, by proteins produced by the developing conceptus (inner cell mass and extraembryonic membranes). We hypothesized that this common process in early pregnancy in eutheria may be facilitated by highly conserved conceptus‐derived proteins such as macrophage capping protein (CAPG). We propose that CAPG may share functionality in modifying the transcriptome of the endometrial epithelial cells to facilitate receptivity to implantation in species with different implantation strategies. A recombinant bovine form of CAPG (91% sequence identity between bovine and human) was produced and bovine endometrial epithelial (bEECs) and stromal (bESCs) and human endometrial epithelial cells (hEECs) were cultured for 24 hours with and without recombinant bovine CAPG (rbCAPG). RNA sequencing and quantitative real‐time PCR analysis were used to assess the transcriptional response to rbCAPG (Control, vehicle, CAPG 10, 100, 1000 ng/mL: n = 3 biological replicates per treatment per species). Treatment of bEECs with CAPG resulted in alterations in the abundance of 1052 transcripts (629 increased and 423 decreased) compared to vehicle controls. Treatment of hEECs with bovine CAPG increased expression of transcripts previously known to interact with CAPG in different systems ( CAPZB, CAPZA2, ADD1, and ADK ) compared with vehicle controls ( P < .05). In conclusion, we have demonstrated that CAPG, a highly conserved protein in eutherian mammals, elicits a transcriptional response in the endometrial epithelium in species with different implantation strategies that may contribute to pregnancy success.